Pesticides Usage in the Soil Quality Degradation Potential in Wanasari Subdistrict, Brebes, Indonesia - Tri Joko; Sutrisno Anggoro; Henna Rya Sunoko; Savitri Rachmawati (Applied and Environmental Soil Science)
Uncontrolled application of pesticides can contaminate soil and may kill other nontarget organisms. This study aims to determine the usage pattern of pesticides by farmers in Wanasari Subdistrict and study the soil quality degradation potential. This study was a quantitative and qualitative research. Sources of data were collected from observation, questionnaire, and in-depth interview methods. The respondents were shallot farmers who planted shallot during 2013–2016 (n=60). In-depth interview was done with three respondents from the local agricultural extension center (BPP). This study found that there were some different types of insecticides and fungicides that were used in every planting season. The farmers applied pesticides in large amount once every three or four days. They mixed minimally three insecticides and fungicides types about 30–40 ml for each type. Organophosphate residues that were found in soil samples were methidathion residue about 0.014 mg/kg, malathion residue ranging around 0.1370–0.3630 mg/kg, and chlorpyrifos residue in the range of 0.0110–0.0630 mg/kg. The excessive application of pesticides showed the land degradation potential. Soil quality laboratory testing is recommended to ensure the agricultural land condition. Routine assessment of soil quality and pesticide usage control is recommended to keep sustainable ecosystem.